Gender effects in hedge funds performance - GAN, Karen Yoke Wah (Institutional Knowledge at Singapore Management University, 2016)
This paper shows that after controlling for total risks (as funds do not typically hold a completely large diversified portfolio) across different funds, female-managed funds appear to perform better in certain circumstances. For example, female-managed hedge funds perform better during post-crisis times, for investments using the Relative Value Style and also when investments are in the Asia excluding Japan region. However, there are still many conditions in which male-managed funds seem to perform better. Namely, male-managed funds performed significantly positive in the Relative Value, Security Selection, and Multiprocess Styles, notably during the pre-crisis period and also when investments are in the "America" and "Others" regions. The study also shows that females definitely do not like to take risks and female-managed funds have lesser inflows relative to male-managed funds, especially when the funds' returns are small. Moreover, fund flows into and out of female-managed funds are more sensitive to the return outcomes.